Reduced Proliferative Potential with Conserved Stem/Stromal Phenotype of Human Umbilical Cord Mesenchymal Stem Cells in Placental Syndromes: A Prospective Cohort Study - Luigi Marino; Maria Antonietta Castaldi; Caterina Fulgione; Salvatore Giovanni Castaldi; Paola Manzo; Valentina Giudice; Francesca Picone; Maria Rosaria Campitiello; Mario Polichetti; Maurizio Guida; Carmine Selleri; Bianca Serio (IMR Press, 2023)
Background: Pathophysiology of placental syndromes is still unclear, and umbilical cord-derived mesenchymal stem cells (UC-MSCs) might play a role in the development of these syndromes. In this prospective cohort study, we evaluated proliferative abilities of two types of UC-MSCs, Wharton's Jelly MSCs (WJ-MSCs) and cord blood MSCs (CB-MSCs), in placental syndromes. Methods: A total of 16 cord blood and umbilical cord samples were seeded and cultured until MSC growth potential exhaustion. Cumulative population doublings were employed for studying growth potential, and flow cytometry immunophenotyping for verification of mesenchymal markers. Results: In our prospective cohort study, on one hand CB-MSCs from pathological pregnancies showed a significant reduction of growth potential, on the other hand WJ-MSCs showed a trend toward higher growth potential. This trend is consistent with the well-known faster-growing phenotype of WJ-MSCs under low oxygen atmosphere. Moreover, it's well understood that chronic hypoxia is a main feature of both intrauterine growth restriction (IUGR) and preeclampsia, thus, our data perfectly match with the well-known clinical characteristics. Conclusions: Growth potential of CB-MSCs obtained from placental syndromes tended to be reduced compared to that of MSCs from healthy pregnancies. Our results need to be confirmed in larger in vitro studies, as a higher number of CB- and WJ-MSC would better clarify pathophysiology of placental syndromes.